Natural Regeneration in the Tropical Deciduous Forest Ecosystem of Godavari Valley in Warangal Region of Telangana, India - Gopalkrishna, P.; Suthari, Sateesh; Raju, Vatsavaya S. (Indian Forester, 2018)
The regeneration, recruitment and succession of tree species were studied in three vegetation zones of Godavari valley in Warangal region, Telangana. The regeneration ability of the individual forest species was observed zone-wise of mature individuals in proportion to the saplings and seedlings to predict the future vegetation of a tropical deciduous forest ecosystem. The study prospects the changes in the native species composition in forest zone-wise. The vegetation structure of Tectona- Terminalia zone will remain unchanged, if protected, as it was being distant to populace and proximate to river Godavari and also better protected being under Eturnagaram Wildlife Sanctuary. Within this vegetation zone, the threat to teak is imminent and it may be replaced by Cleistanthus collinus, a species of far less economic value. Madhuca- Terminalia-Haldina zone is with no saplings of prime species but for those of Terminalia. The absence of saplings and seedlings of Madhuca indica is due to harvesting of its seed for oil by the ethnic people. Terminalia- Hardwickia zone may also remain unchanged though Terminalia species show better regeneration. The ecological changes due to disturbance gradients have resulted in succession of different species other than those of the naturally occurring along the environmental gradients within the watershed.